PELATIHAN MODEL PEMBELAJARAN BERDIFERENSIASI DALAM IMPLEMENTASI KURIKULUM MERDEKA SEKOLAH DASAR DI KECAMATAN RANCAKALONG KABUPATEN SUMEDANG - Agus Mulyanto; Tita Agustini; Sylviana Stefanie; Riska Irnawati (LPPM Universitas Bina Bangsa, 2023)
After the implementation of PKM differentiated learning model training in the implementation of the independent curriculum for elementary schools in Rancakalong District, Sumedang Regency, it is hoped that teachers can understand the basic concepts of differentiated learning in the Implementation of the Independent Elementary School Curriculum, teachers can plan differentiated learning models in schools appropriately, appropriately, and effectively, and so that they have an impact on improving the quality of learning by implementing differentiated learning in each school. As one of the spearheads of education, teachers are obliged to create a quality learning system for students. Because basically education has a responsibility in realizing quality human resources, especially preparing students as successors of future development who are competent, independent, critical, creative and able to solve the problems they face. This PKM activity is also used as a space to meet and exchange ideas and experiences with the progress and development of education in the digital era